Mycobacteria-Specific Mono- and Polyfunctional CD4+ T Cell Profiles in Children With Latent and Active Tuberculosis: A Prospective Proof-of-Concept Study - Tebruegge, Marc; Ritz, Nicole; Donath, Susan; Dutta, Binita; Forbes, Benjamin; Clifford, Vanessa; Zufferey, Christel; De Rose, Robert; Robins-Browne, Roy M.; Hanekom, Willem; Graham, Stephen M.; Connell, Tom; et al. (Frontiers in Immunology, 2019)
Background: Current immune-based TB tests, including the tuberculin skin test (TST) and interferon-gamma release assays (IGRA), have significant limitations, including the inability to distinguish between latent TB infection (LTBI) and active TB. Few biomarkers with the potential to discriminate between these two infection states have been identified. Objective: To determine whether functional profiling of mycobacteria-specific T cells can distinguish between TB-infected and -uninfected children, and simultaneously discriminate between LTBI and active TB. Methods: 149 children with suspected active TB or risk factors for LTBI were recruited at the Royal Children’s Hospital Melbourne. Whole-blood stimulation assays, using ESAT-6, CFP-10, PPD and heat-killed M. tuberculosis as stimulants, were done, followed by intracellular cytokine staining and flow-cytometric analysis. Results: 82 participants in the well-defined diagnostic categories ‘uninfected individuals’ (asymptomatic, TST 0 mm/IGRA-; n=61), LTBI (asymptomatic, TST ≥10 mm / IGRA+, normal chest radiograph; n=15), or active TB (microbiologically-confirmed (n=3) or fulfilling stringent criteria (n=3)) were included in the final analysis. The proportions of mycobacteria-specific single-positive TNF-α+ and double-positive IFN-γ+/TNF-α+ CD4+ T-cells were significantly higher in participants with active TB than in those with LTBI and uninfected individuals. Additionally, the frequency of IL-17-expressing CD4+ T-cells, predominately with single-positive IL-17+ and double-positive IL-2+/IL-17+ phenotypes, was higher in participants with active TB than in the other two groups. Conclusions: The frequencies and functional profiles of mycobacteria-specific CD4+ T cells differ significantly both between TB-infected and TB-uninfected children, and between LTBI and active TB. Although confirmation in further studies will be required, these findings indicate that functional profiling of mycobacteria-specific CD4+ T cells could potentially be exploited for novel immune-based TB assays that enable the distinction between infection states based on a blood sample alone.